EXAMINATION MALPRACTICE IN HIGHER EDUCATION: THE SALIENCE OF UNDERGRADUATE'S WRITING APPREHENSION - Oga, Raphael (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
An examination is a ubiquitous part of the educational system of every society. However, the examination process in academia has been marred by an increasing trend of examination malpractice. Indeed, previous studies have underscored the patterns and correlate of examination malpractice in the educational sector. However, little is known regarding the effect of writing-related emotional state on exam misconduct. The current paper examined the correlation between writing apprehension and examination malpractice. One hundred and eighty-seven (n=187) undergraduates enrolled in a public higher institution in Enugu state participated in the study. The respondents completed self-report measures of the Second Language Writing Anxiety Inventory (SLWAI) and Academic Dishonesty Scale. The study adopted a correlational research model for data analysis. The result demonstrated a significant positive correlation between writing anxiety and examination malpractice in undergraduates, r (185) = .31, p < .001, with writing concern contributing about 21% of the variation in examination malpractice. The study concludes that writing apprehension is a significant determinant of cheating in higher education.